Prevalence of Toxoplasma gondii and Associated Risk Factors among People Living with HIV at Gondar University Hospital, Northwest Ethiopia. (12th August 2013) - Muluye, Dagnachew; Wondimeneh, Yitayih; Belyhun, Yeshambel; Moges, Feleke; Endris, Mengistu; Ferede, Getachew; Yitayew, Gashaw; Negese, Digsu
Abstract : Background . Toxoplasma gondii is an obligate intracellular protozoan parasite and is a major opportunistic pathogen in immune-compromised hosts. This study assessed the prevalence of T. gondii and associated risk factors among people living with HIV. Methods and Materials . A cross-sectional study was carried out among people living with HIV attending Gondar University Hospital. A structured and pretested questionnaire was used to collect sociodemographic factors, and 10mL of venous blood was collected for anti- Toxoplasma antibody test and determination of CD4 levels. Serum was tested in duplicate for anti- Toxoplasma antibody using rapid slide agglutination test. Results . A total of 170 study subjects were enrolled in the study. Seroprevalence of T. gondii among the study participants was 76.5% (95% CI: 69.0–82.8). High proportions of seropositive individuals (64.7%) were found under the child bearing age groups. The mean CD4+ lymphocyte count of HIV monoinfected participants was495.7 ± 334 cells/mm 3 while coinfected study participants had mean CD4+ lymphocyte count of403.5 ± 218.7 cells/mm 3 withP value of 0.01. Conclusion . The seroprevalence of T. gondii among people living with HIV was high. Cautious followup of HIV-positive patients is needed to prevent development of toxoplasmic encephalitis and other related complications.